The Development of Spinning Wheel Media for Addition and Subtraction Learning in Grade 1 of SDN 18 Sitiung - Filahanasari, Eka; Saputra, Agus; Mita, Mita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by students' lack of focus during lessons, the limited variety of learning media, the predominance of lecture-based teaching methods, and the heavy reliance on LKS (student worksheets) with minimal use of instructional aids such as learning media. Additionally, the school had never used the spinning wheel media for teaching addition and subtraction. To address these issues, the researcher aimed to develop a spinning wheel learning medium for addition and subtraction material, enrich the available learning media at the school, and produce a learning medium that is valid, practical, and effective. This study uses the Research and Development (R&D) approach, applying the ADDIE development model which consists of: Analysis, Design, Development, Implementation, and Evaluation. The results of this research and development process produced a teaching material in the form of a spinning wheel media for addition and subtraction, designed for Mathematics learning in Grade 1 at SDN 18 Sitiung. Validation was conducted by three validators. The teaching module validation test received a score of 80%, material validation 92%, media validation 85%, and language validation 100% all categorized as valid. In terms of practicality, the spinning wheel media received a score of 93% from teachers and 94% from students, classified as practical. The effectiveness test, conducted with 15 students using the developed spinning wheel media during learning, showed an average score of 86.66%, categorized as effective.